Adhesive Compositions based on Heptene-1 Copolymer with Maleic Anhydride - F. A. Amirov; R.E. Mammadova; N. A. Guliyeva, (International Journal of Sciences: Basic and Applied Research (IJSBAR), 2024)
Adhesive compositions based on hepten-1-maleic anhydride co-polymer and ED-16 epoxide resin were prepared and some physical and physico-chemical properties of these adhesive compositions were determined. The ability of the prepared adhesive composition to bond aluminum and steel plates was also studied. Adhesive compositions of hepten-1-maleic anhydride copolymer and ED-16 epoxy resin in different ratios (10, 15, 20, 25, 30 s.c. copolymer to 100 s.c. ED-20 epoxide resin) were prepared. Curing of ED-16 epoxy resin with co-polymer (CP) was studied and the effect of temperature and amount of co-polymer on curing was determined. The adhesive properties of aluminum and steel plates were studied Adhesive compositions based on hepten-1-maleic anhydride co-polymer and ED-16 epoxide resin were prepared and some physical and physico-chemical properties of these adhesive compositions were determined. The ability of the prepared adhesive composition to bond aluminum and steel plates was also studied. Adhesive compositions of hepten-1-maleic anhydride copolymer and ED-16 epoxy resin in different ratios (10, 15, 20, 25, 30 s.c. copolymer to 100 s.c. ED-20 epoxide resin) were prepared. Curing of ED-16 epoxy resin with co-polymer (CP) was studied and the effect of temperature and amount of co-polymer on curing was determined. The adhesive properties of aluminum and steel plates were studied by hardening under different conditions. It was determined that the strength of the adhesive compositions prepared in different mass ratios of joint polymer and ED-16 epoxy resin for aluminum plates with a ratio of ED-16:CP=100:25 to fracture resistance. was higher for When the adhesive composition with this composition is cured at 160, 180, 200 0 C for 3 hours, the strength against sliding breakage for duralumin plates were 24.8, 26.2 and 25.8 MPa. The tensile strength ¬and dielectric properties of the adhesive composition prepared in the ratio of ED-16:CP=100:25 were determined. by hardening under different conditions. It was determined that the strength of the adhesive compositions prepared in different mass ratios of joint polymer and ED-16 epoxy resin for aluminum plates with a ratio of ED-16:CP=100:25 to fracture resistance. was higher for When the adhesive composition with this composition is cured at 160, 180, 200 0 C for 3 hours, the strength against sliding breakage for duralumin plates were 24.8, 26.2 and 25.8 MPa. The tensile strength ¬and dielectric properties of the adhesive composition prepared in the ratio of ED-16:CP=100:25 were determined.